Representasi Maskulinitas Tokoh Utama dalam Film Persahabatan Bagai Kepompong 2021 - Annisa Fitria Ramadhani; Catur Suratnoaji (Universitas Merdeka Malang, 2021)
The research aims to illustrate and understand the meaning of the representation of masculinity of the main character in the film